Sebuah Sebuah Analisis Perilaku Impulsif Karyawan - Panji Hidayatulloh; Chandra Arifianto (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
The purpose of this study was to analyze the impulsive behavior of employees in response to company policies. This research was conducted using a qualitative approach as a research procedure that produces descriptive data in the form of written or spoken words from 8 informants, namely employees of PT. Adhimix Precast Indonesia plant BSD 1, South Tangerang. The interactive model used in this study includes data collection, data reduction, data exposure, and drawing conclusions. The results obtained indicate that impulsive behavior that occurs can be in the form of acceptance or rejection of employees against policies issued by the company when they find policies that are felt to affect them, where the impulsive behavior that occurs is still at a safe level.